First Morning Pregnanetriol and 17-Hydroxyprogesterone Correlated Significantly in 21-Hydroxylase Deficiency - Itonaga, Tomoyo; Izawa, Masako; Hamajima, Takashi; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2022)
Background: Biochemically monitoring 21-hydroxylase deficiency (21-OHD) is challenging. Serum/blood 17-hydroxyprogesterone (17OHP) measurements are normally used for this purpose. Urinary pregnanetriol (PT), a urinary metabolite of 17OHP, may also be used. Based on auxological data, we previously reported that the optimal first morning PT value fell in the range of 2.2–3.3 mg/gCr (95% confidence interval of the mean) and 0.59-6.0 mg/gCr (10th – 90th percentile) for monitoring 21-OHD treatment. No report thus far has directly compared the first morning urinary PT value with the 17OHP value at various times during the day. Objective: To explore the correlation between the first morning urinary PT value before glucocorticoid administration and the serum/blood 17OHP value at three time points, namely, before and two and four hours after glucocorticoid administration. Design: This was a prospective study done at two children’s hospitals. Methods: In total, 25 patients with 21-OHD aged 3-25 years were recruited. Their urinary PT levels and 17OHP levels were measured for three days within a total period of one week. The first morning PT value was collected on all three days. Dried blood spots and serum were used to measure 17OHP. Results: The range for the first morning PT value for all the samples (n=69) was 0.10-56.1 mg/gCr. A significant, positive correlation was found between the first morning PT and 17OHP values before medication (r=0.74, p<0.01), but none was observed between the first morning PT and 17OHP values after medication. Conclusions: The first morning PT correlated significantly with 17OHP only before the morning medication. Measuring the first morning PT value may be more practical and useful for monitoring 21-OHD biochemically.